Implementasi Kebijakan Normalisasi pada Situasi Pandemi Covid-19: Studi Kasus pada Kegiatan Keagamaan di Pondok Pesantren Assalafi Al Fithrah Surabaya - Aprilia Santini (Journal Politique, 2023)
The phenomenon that occurs Pandemic Covid-19 causes the disruption of some activities in Islamic boarding schools including in carrying out religious activities. The purpose of this study was (1) to explain the implementation of the normalization policy in the Covid-19 pandemic situation in religious activities at the Assalafi Al Fithrah Islamic Boarding School. (2) and know the factors that support and inhibit the implementation of new normal policies in the boarding school. This study uses a descriptive qualitative method with a case study approach. The theory used in this study is the theory of implementing the Donald Van Meter policy and Van Horn. The results of this study indicate that in the implementation of normalization policies in the Covid-19 pandemic situation (case study in religious activities at the Assalafi Al Fithrah Surabaya Islamic Boarding School). Influenced by six factors, among others, the standard / size of policy, communication, resources, dispositions, bureaucratic structures and conditions, social, economic and political. Supporting Factors Implementation of Normalization Policies Pandemic Pandemic Covid-19 (Case Study of Religious Activities at the US Salafi Al Fithrah Surabaya Islamic Boarding School) is coordination and use of technology. While the inhibiting factor is the budget resource, the awareness of the surrounding community is low, and supervision is not optimal.